The pursuit of happyness - Black, Todd.; Blumenthal, Jason; Lassiter, James; Smith, Will, 1968-; Tisch, Steve; Zee, Teddy; Conrad, Steve; Muccino, Gabriele; Smith, Jaden, 1998-; Newton, Thandie, 1972-; Howe, Brian (Actor).; Karen, James, 1923-; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2007)
In 1981, Chris Gardner was a struggling salesman. His wife worked double shifts to support the family including their young son, Christopher. In the face of this difficult life, Chris has the desperate inspiration to try for a stockbroker internship where one in twenty has a chance of a lucrative full time career. Even when his wife leaves him because of this choice, Chris clings to this dream. The odds become more daunting by the day. Together, father and son struggle through homelessness, jail time, tax seizure and the overall punishing despair in a quest that would make Gardner a respected millionaire.
DVD release of a 2006 motion picture.
Special features: Making pursuit; Father and son; The man behind the movie; Inside the Rubik's Cube; director's commentary.
Director of photography, Phedon Papamichael ; editor, Hughes Winborne ; music, Andrea Guerra.
Will Smith, Jaden Christopher Syre Smith, Thandie Newton, Brian Howe, James Karen, Dan Castellaneta, Kurt Fuller, Takayo Fischer.
MPAA rating: PG-13; for some language.
DVD; region 1; widescreen (2.40:1) presentation.
Keywords: Sales personnel -- United States -- Drama; Internship programs -- United States -- Drama; Stockbrokers -- United States -- Drama; Fathers and sons -- United States -- Drama; Dreams -- Drama; Despair -- Drama; Millionaires -- United States -- Drama; Vendedores -- Estados Unidos -- Teatro; Padre e hijo -- Estados Unidos -- Teatro; Sales personnel -- United States -- Drama; Internship programs -- United States -- Drama; Stockbrokers -- United States -- Drama; Father-son relationship -- United States -- Drama; Dreams -- Drama; Despair -- Drama; Millionaires -- United States -- Drama; Despair; Dreams; Fathers and sons; Internship programs; Millionaires; Sales personnel; Stockbrokers; United States; Feature films; Biographical films; Melodrama; Biographical -- Feature; Melodrama -- Feature; Feature films; Biographical films; Melodrama; Videorecordings for the hearing impaired; Videodiscs; DVD-Video discs; Biographical films; Drama; Feature films; Melodrama